THE IMPACT OF THE KINEMATIC PARAMETERS OF BOUNCE AND PITCH MOTIONS OF SPRUNG MASS ON WHEELED VEHICLES HANDLING - Оleg LYASHUK; Mariya SOKIL; Yuriy VOVK; Oleg TSON; Volodymyr DZYURA (Scientific Journal of Silesian University of Technology. Series Transport)
The impact of the kinematic parameters of bounce and pitch motions of wheeled vehicles’ (WVs’) sprung mass (SM) with non-linear power characteristics of the cushion system on vehicles handling is studied. The dependence of the critical value of the dynamic steering angle of directive wheels on the amplitude of bounce and pitch motions and the kinematic parameters of motion is developed. It is proven that the limit value of the dynamic steering angle of directive wheels is reduced during acceleration, and vice versa (it increases during braking, while the bounce and pitch motions are significantly reduced).